A influência do pensamento teológico no projeto filosófico inicial de Martin Heidegger - Mendes, Eric Ewans (2018)
Heidegger's academic life began in theology, migrating to philosophy from the year 1912 and converting to a conciliatory spirituality (free Protestantism associated with the preservation of elements of Catholic Christian spirituality) in 1919. During this time, he criticizes theology for having adopted metaphysics to work the knowledge of God, presenting a supreme being and impersonal. The influences of St. Paul, St. Augustine, Luther, Kierkegaard, and others contributed to the development of his early philosophical project, which resulted in his most important work: Being and Time (1927), a work in which it is possible to note the extraction of Christian thought and a strong structural relation to the interpretation he himself [Heidegger] makes of the proto-Christian life presented by Paul in the two Epistles to the Thessalonians. In the same way, his analysis of Dasein exerted a strong influence on Catholic and Protestant theological thinking and also on the philosophy of religion, mainly in the person of Bernhard Welte. In Catholic theology, it has the main names are Karl Rahner, Edith Stein and Max Müller. On the Protestant side, Klaus Berger, Wolfhart Pannenberg, Paul Tillich, and Rudolf Bultmann, with whom Heidegger maintained a fraternal and intellectual relationship from the time they met in Marburg, which lasted for fifty years, recorded in the correspondences exchanged between them. This intellectual relation has resulted in the adoption of Heidegger's analysis of Dasein by Bultmann in his existential theology, which led him to the hermeneutic method known as Demythologization [Entmythologisierung], which is intended to remove the mythological concerns of the Bible for the understanding of true faith.